ACo2O4 (A=Ni, Zn, Mn) nanostructure arrays grown on nickel foam as efficient electrocatalysts for oxygen evolution reaction. (2nd August 2018) - Gong, Yaqiong; Pan, Hailong; Xu, Zhoufeng; Yang, Zhi; Lin, Yu; Zhang, Meilin
Abstract: Developing highly efficient, low-cost and superior stable electrocatalysts for the oxygen evolution reaction (OER) is essential for coping with global energy shortage and environmental crisis. In this article, ACo2 O4 /NF (A = Mn, Zn, Ni) composites were synthesized via a facilely hydrothermal and calcination method and used as electrocatalytic water oxidation catalysts. The hybrid structure, chemical composition, oxidation state and surface morphology of ACo2 O4 /NF (A = Mn, Zn, Ni) has been confirmed by powder X-ray diffraction (XRD), energy dispersive X-ray (EDX), X-ray photoelectron (XPS), scanning electron microscopy (SEM), transmission Electron Microscope (TEM) and Brunaure-Emmett-Teller (BET) analysis. Such self-supported NiCo2 O4 /NF hybrid shows a smaller overpotential of 271 mV at current density of 10 mA cm −2 in 1 M KOH, which is comparable to most reported NiCo2 O4 materials (monomer or composite) for OER. Influence on catalytic activity of doping different metal ions in ACo2 O4 /NF was investigated systematically for the first time. Improved electrocatalytic activity of NiCo2 O4 /NF is attributed to the special homogeneous urchin-like structure and porous property. Highlights: Nickel foam provides large specific surface area and benefits for electron transfer. Different metal ions Doped ACo2 O4 display discrepant OER performance. Excellent OER activity of NiCo2 O4 /NF derives from electron orbit and synergistic effect.